Clinical and Neuroimaging Outcomes of Direct Thrombectomy vs Bridging Therapy in Large Vessel Occlusion: Analysis of the SELECT Cohort Study. (8th June 2021) - Sarraj, Amrou; Grotta, James; Albers, Gregory W.; Hassan, Ameer E.; Blackburn, Spiros; Day, Arthur; Sitton, Clark; Abraham, Michael; Cai, Chunyan; Dannenbaum, Mark; Pujara, Deep; Hicks, William; et al.
Abstract : Objective: To evaluate the comparative safety and efficacy of direct endovascular thrombectomy (dEVT) compared to bridging therapy (BT; IV tissue plasminogen activator + EVT) and to assess whether BT potential benefit relates to stroke severity, size, and initial presentation to EVT vs non-EVT center. Methods: In a prospective multicenter cohort study of imaging selection for endovascular thrombectomy (Optimizing Patient Selection for Endovascular Treatment in Acute Ischemic Stroke [SELECT]), patients with anterior circulation large vessel occlusion (LVO) presenting to EVT-capable centers within 4.5 hours from last known well were stratified into BT vs dEVT. The primary outcome was 90-day functional independence (modified Rankin Scale [mRS] score 0–2). Secondary outcomes included a shift across 90-day mRS grades, mortality, and symptomatic intracranial hemorrhage. We also performed subgroup analyses according to initial presentation to EVT-capable center (direct vs transfer), stroke severity, and baseline infarct core volume. Results: We identified 226 LVOs (54% men, mean age 65.6 ± 14.6 years, median NIH Stroke Scale [NIHSS] score 17, 28% received dEVT). Median time from arrival to groin puncture did not differ in patients with BT when presenting directly (dEVT 1.43 [interquartile range (IQR) 1.13–1.90] hours vs BT 1.58 [IQR 1.27–2.02] hours, p = 0.40) or transferred to EVT-capable centers (dEVT 1.17 [IQR 0.90–1.48] hours vs BT 1.27 [IQR 0.97–1.87] hours, p = 0.24). BT was associated with higher odds of 90-day functional independence (57% vs 44%, adjusted odds ratio [aOR] 2.02, 95% confidence interval [CI] 1.01–4.03, p = 0.046) and functional improvement (adjusted common OR 2.06, 95% CI 1.18–3.60, p = 0.011) and lower likelihood of 90-day mortality (11% vs 23%, aOR 0.20, 95% CI 0.07–0.58, p = 0.003). No differences in any other outcomes were detected. In subgroup analyses, patients with BT with baseline NIHSS scores <15 had higher functional independence likelihood compared to those with dEVT (aOR 4.87, 95% CI 1.56–15.18, p = 0.006); this association was not evident for patients with NIHSS scores ≥15 (aOR 1.05, 95% CI 0.40–2.74, p = 0.92). Similarly, functional outcomes improvements with BT were detected in patients with core volume strata (ischemic core <50 cm 3 : aOR 2.10, 95% CI 1.02–4.33, p = 0.044 vs ischemic core ≥50 cm 3 : aOR 0.41, 95% CI 0.01–16.02, p = 0.64) and transfer status (transferred: aOR 2.21, 95% CI 0.93–9.65, p = 0.29 vs direct to EVT center: aOR 1.84, 95% CI 0.80–4.23, p = 0.15). Conclusions: BT appears to be associated with better clinical outcomes, especially with milder NIHSS scores, smaller presentation core volumes, and those who were "dripped and shipped." We did not observe any potential benefit of BT in patients with more severe strokes. Trial Registration Information: ClinicalTrials.gov Identifier : NCT02446587. Classification of Evidence: This study provides Class III evidence that for patients with ischemic stroke from anterior circulation LVO within 4.5 hours from last known well, BT compared to dEVT leads to better 90-day functional outcomes.